Estudo de indicadores ambientais de blocos cerâmicos com base em avaliação do ciclo de vida, considerando o contexto brasileiro - Vinhal, Laís David (2016)
The construction sector is one of the sectors that most require natural resources and generate waste throughout the production chain. In this sense, given the need to preserve the environment and natural resources for future generations, the industry needs to improve the environmental performance of its operations chain. In order to achieve effective improvements by the actions developed by the sector, these actions need to be based on information about the environmental performance that are objective and verifiable. One of the methods that allow the collection of environmental information is Life Cycle Assessment (LCA), which is one of the main tools of environmental impact assessment for the lifecycle of products and systems. The LCA allows to evaluate the impacts of raw material extraction, manufacturing process, use and disposalt. In this context, a study of the manufacturing process of structural ceramic blocks (cradle to factory gate) was conducted, aiming to analyze its main impacts and processes that contribute most to these environmental impacts. To conduct this study data collection was performed in two plants located in the State of São Paulo. Based on data collected locally and on the international database Ecoinvent®, the life cycle inventory (LCI) was drawn up with the necessary adaptations to represent the local context. Life cycle impact assessment (LCIA) was carried out using the following methods: CML 2002, Edip 97, USEtox and IPCC 2013. Based on the LCIA results, it was possible to identify the processes that contributed to each of the impacy categories analyzed, with the electricity being the process that most contributed to all categories. But the fuel used in the burning of the blocks, in turn, did not generate significant environmental impacts due to factories studied using biomass. Therefore, this study allowed to evaluate the magnitude and importance of the environmental impacts generated by the manufacture of ceramic bricks and also to characterize the environmental performance of ceramic bricks based on LCA.